Economic and functional changes in the largest villages in Poland at the end of the 20th and the beginning of the 21st century - Sokołowski Dariusz (Bulletin of Geography. Socio-Economic Series)
The article deals with selected aspects of the economic structure and functions of the largest villages in Poland. The main aim of the study is to investigate the diversity and changes that can be observed to have happened since before the fall of Communism in Poland. Large villages with populations exceeding 5,000 inhabitants are located in the same part of the rural–urban continuum as small towns, including many poviat (1) seats. For this reason, they are an interesting comparative category of settlement units. The study was based on a source database from the end of the last century and on contemporary public data from the REGON database. The comparison is based not only on various data, but also uses various research methodologies.